2018
DOI: 10.1111/bmsp.12137
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic tree model for polytomous responses with multiple strategies

Abstract: Constructed-response items have been shown to be appropriate for cognitively diagnostic assessments because students' problem-solving procedures can be observed, providing direct evidence for making inferences about their proficiency. However, multiple strategies used by students make item scoring and psychometric analyses challenging. This study introduces the so-called two-digit scoring scheme into diagnostic assessments to record both students' partial credits and their strategies. This study also proposes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…Third, only the dichotomous scoring item and dichotomous attribute were modeled in the proposed model. It would be meaningful and practical to extend the current model to consider polytomous scoring items (e.g., Ma, 2019;von Davier, 2008) and polytomous attributes (e.g., Karelitz, 2008;Zhan, Wang, & Li, 2019). Fourth, notably, the generalizability of the findings of this study is dependent upon the limitations of the design of the simulation studies, such as a fixed number of attributes and assuming the Q-matrix is correct.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…Third, only the dichotomous scoring item and dichotomous attribute were modeled in the proposed model. It would be meaningful and practical to extend the current model to consider polytomous scoring items (e.g., Ma, 2019;von Davier, 2008) and polytomous attributes (e.g., Karelitz, 2008;Zhan, Wang, & Li, 2019). Fourth, notably, the generalizability of the findings of this study is dependent upon the limitations of the design of the simulation studies, such as a fixed number of attributes and assuming the Q-matrix is correct.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…We also found that the Q‐matrix in the real data was complete based on the procedure of Köhn and Chiu (), indicating that all latent classes are distinguishable. Nevertheless, the evaluation of local identifiability of the GMS‐LLM, by checking whether the information matrix is positive definite as in von Davier () and Ma (), failed as a result of numerical problems caused by the boundary estimates. A possible approach to boundary solutions is to employ the posterior mode estimation, which has been discussed by DeCarlo () in the CDM contexts.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Last, the GMS‐CDMs can be viewed as a variant of the DTM of Ma (), which incorporates CDMs into tree models to accommodate multiple strategies for polytomous response data from constructed‐response items. Similar to the DTM approach, the GMS‐CDMs proposed in this paper can be presented using the tree diagram, as shown in Figure , where the first node (i.e., X 0 ) represents the task for strategy selection with M possible outcomes for M strategies.…”
Section: A Generalized Multiple‐strategy Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Attributes are discrete in nature rather than continuous, with usually only two levels indicating if the examinees mastered or did not master each specific attribute. CDM is a very active area of research (e.g., [6,7]). Some of the latest developments are in the area of cognitive diagnostic CAT (CD-CAT).…”
Section: Introductionmentioning
confidence: 99%